Prisoners’ Round: Examining the Literature on Recreation and Exercise in Correctional Facilities - Ambrose, Mallory A.; Rosky, Jeffrey W. (International Journal of Criminology and Sociology, 2013)
Opposition to correctional recreation programs expresses safety concerns for staff and argues that removal of these programs enhances the retributive nature of prison and jail. Supporters cite the health benefits for inmates and incentive for better behavior within correctional facilities. Using academic sources and media articles, we found that the available empirical data support the use of these programs. However, public perception appears yet to be swayed by such evidence. Despite this opposition, we recommend that use of physical recreation and exercise programs in correctional facilities should continue to be used within a prescribed rewards system.